Goods Inventory Card System Design Using The Unified Modeling Language (UML) of Department Libraries and Archives at Medan City - Novya Nurfi; Edy Rahman Syahputra; Fachrul Rozi Lubis (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
Government Regulation Number 27 of 2014 concerning Processing of State/Regional Owned Goods is intended to support the development of an area where state assets or goods are held based on the results of an appropriate needs analysis and meet the efficiency principle. Asset management Libraries and Archives Department at Medan City. But until now the local asset management in the Department of Library and Archives Medan City Government has not had asset management information system that supports accordance with Regulation No. 17 Year 2007 Chapter VII of the administration of section 25 which contains the data collection activities, inventory and reporting. Based on the above requires a management information system design goods and assets in order to facilitate the work in developing SIMBADA existing system. The system development process uses Waterfall and UML design methods as system business process development tools. The results of the design has been made known that the design of this system can meet the asset management process in accordance with Regulation No. 17 Year 2007.